Implementasi Metode Zero One Dan Analitycal Hierarchy Process (AHP) Dalam Redesain Kemasan Obat (Study Kasus Pada PT. BPFC) - refo akbar nusantara; Ribangun Bamban Jakaria (SITEKIN: Jurnal Sains, Teknologi dan Industri, 2022)
PT. BPFC started its work in Indonesia since 1971. In general, the company is involved in the pharmaceutical field and continues to innovate in the health sector in Indonesia. Its activities include Generic branded business through prescription, Generic business through DHO and government hospitals, and other pharmaceutical products. The main products managed by PT. BPFC is a generic drug, basically a generic drug is one of the pharmaceutical preparations that has fulfilled pharmacopoeia requirements and goes through the manufacturing process according to Good Manufacturing Practices (CPOB). The Food and Drug Supervisory Agency (BPOM) also supervises these general standards. The purpose of this study is to be able to design exhausts according to specifications by applying the Zero one method and the analyticalcal hierarchy process (AHP) and calculate the time needed to design drug packaging products into specifications by producing products that meet user requirements. One method used in this research is the Zero one method and the analytical hierarchy process (AHP) is the product design development process used to simplify and reduce assembly time, but still focus on the function of the product itself and pay attention to the safety factor of its performance. From this research it is expected to be able to provide an overview to PT BPFC in order to be able to design drug packaging products more effectively and efficiently using the Zero one method and the analyticalcal hierarchy process (AHP)